Entry to OER-Based Material Development Of English For Culinary Purposes - Irzy Lil Iman; Frimadhona Syafri; Fiki Alghadari; Audi Yundayani (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
This study seeks to highlight students' need analysis for English for culinary purposes (ECP) as an entry of open educational resources (OER)-based material development. The participants in the study were two English teachers from a Bekasi vocational school. A semi- structured interview was utilized for data collection. This study found that the learning objective of ECP is to equip students to communicate orally and in writing with clients and other culinary professionals at the A2 or B1 level of English proficiency, within the context of the culinary arts. In addition, the required ECP material should include the following topics: (1) service areas; (2) kitchen utensils; (3) storage room; (4) collaborating as a team; (5) the hazard handling procedure; (6) correspondence activity; (7) le gourmet; (8) ingredients; (9) taking orders. Integration of linguistic features and generic structure should be incorporated into the design of ECP teaching materials to facilitate content-based instruction. The research reveals that OER-based material development for culinary purposes should consider the learning objective, the needs, preferences, and profiles of the students, as well as their English proficiency level. In addition, it is crucial to involve students in the learning process by utilizing OER and authentic material delivered through technology.